GROWTH PERFORMANCE AND ECONOMICS OF RAISING BUFFALO CALVES BY USING PROBIOTICS - G. P. LAKHANI, NAMAN SINGH; A. JAIN B. ROY (Indian Journal of Animal Production and Management, 2017)
An experiment was conducted at Livestock Farm, Adhartal, College of VeterinaryScience and A. H., Jabalpur, N.D.V.S.U., Jabalpur (M.P.). Eighteen Murrah buffalo calves wereselected and were divided into 3 groups having 6 calves in each gruop. Group 1 (Control)was fed with the basal ration, group 2 (T1) was fed with the basal ration with probiotic(Saccharomyces cerevisiae) @5g/animal/day and the group 3 and (T2) was fed with thebasal ration with probiotic (Saccharomyces cerevisiae+ Lactobacillus sporogenes) @ 5g/animal/day. Calf starter (22% DCP and 72% TDN) was provided to all the calves. Besidesthis, adlib green chaffed fodder was provided to the animals. It was found that calves of theT2 group showed significantly (p